Domperidone vs Metoclopramide: Comparative Evaluation of Efficacy in Treating Diabetic Gastroparesis: Domperidone vs Metoclopramide: Efficacy in Treating Diabetic Gastroparesis - Saeed, Asma; Manzar, Adnan; Yousaf, Rizwan; Farooq, Muhammad Junaid; Khurram, Mahaa; Bashir, Zukhrif (Pakistan Journal of Health Sciences, 2026)
Gastroparesis represents a diabetes-related condition that causes diabetic patients to experience nausea, vomiting, and bloating. Objectives: To evaluate the effectiveness of Domperidone and Metoclopramide for gastric emptying improvement and gastrointestinal symptom reduction in patients with diabetic gastroparesis. Methods: A total of participants were n=76. Data collection occurred through a study of diabetes patients with gastroparesis who were given Domperidone (10 mg three times daily) or Metoclopramide (10 mg three times daily) for six weeks. The researchers evaluated gastric emptying half-time (T½) as the main outcome, while considering symptoms of nausea, vomiting, and bloating. The study evaluated both negative side effects and participant medication adherence. Results: The gastric emptying reduction using Domperidone exceeded that of Metoclopramide following administration to patients, as Domperidone decreased T½ from 125.6 ± 18.4 minutes to 98.2 ± 15.6 minutes while Metoclopramide decreased T½ from 124.8 ± 17.9 minutes to 107.5 ± 16.9 minutes (p = 0.04). The patients who received Domperidone reported better decreases in nausea, vomiting, and early satiety symptoms than those who received Metoclopramide (p=0.03, p=0.02, and p=0.04). The occurrence of extrapyramidal symptoms together with QT prolongation proved more common in patients treated with Metoclopramide. Compliance was similar between groups. Conclusions: Diabetic patients with gastroparesis experienced superior gastric motility response and symptom relief after taking domperidone compared to metoclopramide, along with better outcomes regarding extrapyramidal symptom development.